Ability of different adsorbent for removal of Rhodamine B from aqueous solution - Ahmed, Nawzad Noori; AL-Salihi, Kareem Jumaah (Sulaimani Journal for Pure and Applied Sciences, 2019)
Adsorption of Rhodamine B dye on powdered TiO2, zinc oxide (ZnO) and natural Bentonoit clay from aqueous solutions have been studied .The potential for the adsorption of Rhoamine dye at a fixed initial concentration of 5 ppm. The experiments were carried out in a batch system to optimize operation variables initial concentration, effect of time adsorption isotherms. The langmuir and frendlish isotherm equations were applied to the data and values of parameters of these results suggest that the adsorption of (RB) dye on ZnO observed more fit to Freundlich model it means the Rhodamine B adsorbed weakly to the surfaces of ZnO, physical adsorption is achieved between the adsorbed and adsorbent, but the adsorption on TiO2 and bentonite better fit to Langmuir model. Kinetics study was made using lagergreen equation the results show the sorption of Rhodamine B dye uptake on ZnO fitted to first order reaction. And the sorption of RB on TiO2, and Bentonite fitted with second order. The partition coefficient kd for the sorption of RB on TiO2, ZnO and bentonite also determined and shows the value of Kd increases with time until equilibrium and becomes constant. we can conclude that the proportion of RB dye on each adsorbent increase which means that the large number of adsorption sites available with the rate slowing with time as sites fill up. The enthalpy of adsorption of rhodamine B on TiO2, + 4.09 kJ/mol, on ZnO +15.25 kJ/mol and on bentonite +4.01 kJ/mol indicates that the process is endothermic. The thermodynamic quantities ΔG°, ΔH°, and ΔS°, for the adsorption of rhodamine B dye on the surfaces of TiO2, ZnO and bentonite have been calculated. The result shows that the value of ΔG° decrease with an increase in temperature indicates that the adsorption process is more favorable at high temperature. Whereas the positive value of ΔS° as a result of rhodamine B adsorption due to an increased degree of freedom in the system and indicates high affinity of the adsorbent for Rhodamine molecules.
Keywords: adsorption; adsorbent,TiO2; ZnO; bentonite isotherm; partition coefficient; kinetic of heterogeneous reaction